The COVID-19 pandemic in Ireland: An overview of the health service and economic policy response. Issue 4 (December 2020) - Kennelly, Brendan; O'Callaghan, Mike; Coughlan, Diarmuid; Cullinan, John; Doherty, Edel; Glynn, Liam; Moloney, Eoin; Queally, Michelle
Highlights: Very significant effects on health and well-being from the COVID-19 virus and the associated lockdown. As of July 19th, 1, 753 people have died and 25, 766 have tested positive with the virus. Raid growth in new cases and deaths in the first six weeks of the pandemic. Subsequent fall in cases and deaths until late July. Generally a very high level of compliance with public health measures. Abstract: Objectives: To outline the situation in Ireland with regard to the COVID-19 pandemic. Methods: Analyse the evolution of the COVID-19 pandemic in Ireland. Review the key public health and health system responses. Results: Over 1700 people have died with COVID-19 by July 19th while almost 3000 people had been admitted to hospital with COVID-19. A high proportion of the deaths occurred in nursing homes and other residential centres who did not receive sufficient attention during the early phase of the pandemic. Conclusions: Ireland's response to the COVID-19 crisis has been comprehensive and timely. Transparency, a commitment to a relatively open data policy, the use of traditional and social media to inform the population, and the frequency of updates from the Department of Health and the Health Services Executive are all commendable and have led to a high level of compliance among the general public with the various non-medical measures introduced by the government.